The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1139/bcb-2021-0503
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic mobility of individual molecules of alkaline phosphatase

Abstract: The electrophoretic mobilities and catalytic rates of individual molecules of bovine intestinal alkaline phosphatase were determined in CHES and borate buffers of identical pH using a capillary electrophoresis based method. Both properties were found to be heterogeneous. In the presence of CHES, the mobility and rate were found to be −1.9 ± 0.2 × 10−9 m2 V−1 s−1 and 9.8 ± 7.4 × 104 min−1 ( N = 38), respectively. In the presence of borate, the mobility and rate were found to be −6.9 ± 0.5 × 10−9 m2 V−1 s−1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…The Winzor model [2] used suggested that the variance in mobility of the unmodified enzyme could be attributed to relatively small difference in size and effective charge. This is consistent with other studies [13][14][15]. The model gave plausible results for the prediction of changes in size, shape, and charge required to accompany the changes in observed mobilities of -galactosidase caused by labelling.…”
Section: Factors Affecting Electrophoretic Mobilitysupporting
confidence: 91%
See 2 more Smart Citations
“…The Winzor model [2] used suggested that the variance in mobility of the unmodified enzyme could be attributed to relatively small difference in size and effective charge. This is consistent with other studies [13][14][15]. The model gave plausible results for the prediction of changes in size, shape, and charge required to accompany the changes in observed mobilities of -galactosidase caused by labelling.…”
Section: Factors Affecting Electrophoretic Mobilitysupporting
confidence: 91%
“…Previous studies have suggested that the observed heterogeneity in electrophoretic mobility of individual enzyme molecules may result from relatively small differences in shape, size, and charge [13][14][15]. In order to assess this, -galactosidase was subjected to relatively small changes in its size, shape and charge through chemical modification.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation